It’s Not Mysticism, It’s Just Business: Image as an Economic Category for Territorial Development - Lidin, Konstantin (project baikal, 2018)
The image of the place is discussed as a socio-psychological and economic category. The mechanisms of perception of this image are well-known and actively studied. But the results of such studies are insufficiently used in the territorial development practices. The reasons of this lagging are considered in the article.